2011
DOI: 10.1177/0194599811412038
|View full text |Cite
|
Sign up to set email alerts
|

Tympanostomy Tube Placement and Vestibular Function in Children

Abstract: Objective To determine the effect of bilateral myringotomy with tube placement (BMT) on balance in children 4 to 7 years old Study Design Case-control study Setting Tertiary-care academic hospital Subjects and Methods Children with otitis media with effusion (OME) who were scheduled for BMT underwent rotational chair testing (RCT) and computerized dynamic posturography (CDP) preoperatively and at 1, 3, and 6 months postoperatively. Control children without a significant history of middle-ear disease were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…In our cohort, the number of comorbidities was too diffuse to perform any statistical analyses to determine trends on the type of comorbidity for each of the groups with vestibular loss. However, in the list of recorded comorbidities, several are associated with gross motor delay, such as OME, congenital heart defects, and neurologic disorders such as cerebral palsy (Casselbrant, Villardo, & Mandel, 2008;Cohen, Mandel, Furman, Sparto, & Casselbrant, 2011;Jones, Morgan, Shelton, & Thorogood, 2007), which suggests that, when using gross motor function to predict vestibular loss, comorbidities should be considered.…”
Section: Group Comorbidity Interactionmentioning
confidence: 99%
“…In our cohort, the number of comorbidities was too diffuse to perform any statistical analyses to determine trends on the type of comorbidity for each of the groups with vestibular loss. However, in the list of recorded comorbidities, several are associated with gross motor delay, such as OME, congenital heart defects, and neurologic disorders such as cerebral palsy (Casselbrant, Villardo, & Mandel, 2008;Cohen, Mandel, Furman, Sparto, & Casselbrant, 2011;Jones, Morgan, Shelton, & Thorogood, 2007), which suggests that, when using gross motor function to predict vestibular loss, comorbidities should be considered.…”
Section: Group Comorbidity Interactionmentioning
confidence: 99%
“…In this study maternal weight in LTG treated group 'B' was reduced when compared with Control group 'A' and it was very highly significant, However Lamotrigine administration to mother has no effect on food intake, but it may be due to loss of fetuses owning to the treatment with Lamotrigine, the findings are consistent with the observation of [14], when LTG was given on day 7th and 8th at a dose of 25 mg/Kg and 50mg/kg body weight respectively. El-Sayyad et al also observed reduction in maternal body weight when lamotrigine 50 mg /Kg body weight every other day from 6th day of gestation until parturition, was given to albino rats of Wistar strain [15]. This indicates dose related toxic effects on maternal weight gain.…”
Section: Discussionmentioning
confidence: 91%
“…In children 3-6 years with moderate secretory otitis, the average rate of oscillation of the body according to computer stabilometry is disturbed both before and after surgery at 3 months, which is considered by the authors as a sign of latent vestibular dysfunction [16]. In the study of children 47 years with effusion in the middle ear, no differences were found with the control in the tests of Barany but found not significantly higher rocking speed according to posturography [17].…”
Section: Introductionmentioning
confidence: 90%